Didactic Possibilities of Creating an Environment of Individual Approach in the Educational Process - Jamshid Turdiev, (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
It is known that the didactic possibilities of creating an environment of individual approach in the educational process are objects that facilitate direct and indirect knowledge of reality by providing students with sensorimotor stimuli affecting vision, hearing, direct touch, etc.Individual educational environment is a set of conditions that allow students to receive quality education, taking into account their individual characteristics and needs. The article discusses the didactic possibilities of teaching in an individual educational environment.